Penyusunan Alternatif Produksi Bersih Di UKM Batik Cap Kota Pekalongan Studi Kasus pada UKM Agus Wijaya dan UKM Ganesha - Tenny Monika; Aries Susanty; Dyah Ika Rinawati (Industrial Engineering Online Journal, 2012)
Batik is one part of the creative industry of crafting giving big contribution to Gross Domestic Product. Growth of batik industries which more and more its amount generate impact to growth of economics and contamination of environment. This study aim to analyse, identify and compile some cleaner production alternative which is possible applied at Small and Medium Enterprise (SMEs) Batik Cap in Pekalongan. From identifying yielded waste amount and type in each batik production process, in general both SMEs yield the same waste that is liquid waste, solid and gas. Liquid waste represent the biggest waste of  its amount. Identify environmental performance with calculation of index EPI (Environmental Performance Indicator) at two SMEs that is SMEs Agus Wijaya and SMEs Ganesha show negative value each of - 130,83 and - 401,62 meaning that environmental performance both SMEs not yet as according to standard quality of textile liquid waste and batik. From both identifying above compiled cleaner production alternative of waste management that is : collecting the droplets of wax from the process stamping than reuse it, recycle the collected wet wax from pelorodan process, reuse the wastewater from dyeing process, usage of padder machine, reduce the use of synthetic dyes with natural dyes, reuse the water from washing and flushing process as long as 2 days before disposal, construction the malam catcher (kowen), reuse the water from pelorodan process as long as 3 days before disposal and construction the simple Waste Water Treatment Process (WWTP). This formation alternative is expected can minimization the waste which is yielded so that SMEs can take care of environment and conduct efficiency produce concurrently.